PENGARUH PEMBERIAN PANGAN YANG DIFORTIFIKASI TERHADAP PENINGKATAN KONSUMSI GIZI DAN STATUS ANEMI IBU HAMIL1)THE EFFECT OF GIVEN FORTIFIED FOOD ON INCREASING NUTRITION CONSUMPTION AND ANEMIA STATUS OF PREGNANT - , Prihananto; , Rimbawan; , Sandjaja (Pembangunan Pedesaan, 2006)
The objective of this study was to analyze the effect of fortified foods on nutrition consumption and haemoglobin (Hb) status of pregnancy. This study was conducted in three sub-districts, i.e., Leuwiliang, Leuwisadeng and Ciampea. The 140 pregnant mothers from these sub-districts were selected for this study. From 140 pregnant mothers, 70 pregnant mothers were selected to receive fortified foods with multi-nutrients i.e. iron, iodine, zinc, folic acid, vitamin C, and vitamin A, for 6 months and 70 pregnant mothers did not receive any experimental food (control). Product selected as intervention carrier consisted of vermicelli, milk, and biscuit. The results of the study showed:(a) Compliance level of product feeding: bihun 90.72%, biscuit 94.64%, and milk 93.61%, (b) Intervention could improve nutrition consumption and fulfill energy 104% RDA, protein 80.7% iron 98.6% RDA, vitamin A 131% RDA, vitamin C 152.1% RDA, (c) intervention could reduceprevalence of anemia as much as 30% compare with control.